2005
DOI: 10.1021/om050113x
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Elimination of Organic Molecules from Palladium−Diphosphine Complexes

Abstract: The effects governing the rate of reductive elimination of dimethyl ether, acetonitrile, vinyl cyanide, and methyl ethanoate from palladium diphosphine complexes were studied by means of a density functional theory method. Energy barriers, computed as the difference in energy between the reactant and the corresponding transition state using H2P(CH2)2PH2 as model for diphosphine ligands, varied from 38 kcal mol-1 (dimethyl ether) to barrierless elimination of methyl ethanoate, in good agreement with experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 49 publications
4
63
0
2
Order By: Relevance
“…There have been many experimental [11][12] and theoretical studies of the reaction. [50][51][52] Initially, it was concluded that monodentate phosphines favour hydroesterification of ethene to give methyl propanoate, whereas bidentate phosphines lead to polyketones. [9] Subsequently, van Leeuwen showed that the chemoselectivity of the reaction can be…”
Section: Introductionmentioning
confidence: 99%
“…There have been many experimental [11][12] and theoretical studies of the reaction. [50][51][52] Initially, it was concluded that monodentate phosphines favour hydroesterification of ethene to give methyl propanoate, whereas bidentate phosphines lead to polyketones. [9] Subsequently, van Leeuwen showed that the chemoselectivity of the reaction can be…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] We believe that the steric bulk not only prevents the formation of bis-chelates with ligands L3-L5 but also has an effect on either the rate of reductive elimination or on the rate of deactivation. This would explain the fact that these systems become more efficient in the hydrocyanation of styrene (in conversion and enantioselectivity) with increasing steric bulk.…”
mentioning
confidence: 97%
“…[7] A simplified, traditional mechanism involves three steps: 1) the oxidative addition of the halogeno-arene (OA, Scheme 1), [8] 2) the transmetalation with the organozinc derivative, (TM, Scheme 1), [9] and 3) the reductive elimination that forms the biaryl product and regenerates the active Pd 0 species (RE, Scheme 1). [10] To date, only few computational studies have addressed the full catalytic cycle. [11] Most recently, we have incorporated the phosphabarrel-A C H T U N G T R E N N U N G ene ligand 1 (= L in Scheme 1 and 2), in various catalytic processes, such as the Pt-catalyzed hydrosilylation of alkynes, or the Pd-catalyzed Suzuki-Miyaura cross-coupling [a] of chloroarenes at room temperature.…”
mentioning
confidence: 99%